2010
DOI: 10.1128/jvi.00165-10
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Ligands Selected with CD4-Induced Epitopes on Native Dualtropic HIV-1 Envelope Proteins Mimic Extracellular Coreceptor Domains and Bind to HIV-1 gp120 Independently of Coreceptor Usage

Abstract: During HIV-1 entry, binding of the viral envelope glycoprotein gp120 to the cellular CD4 receptor triggers conformational changes resulting in exposure of new epitopes, the highly conserved CD4-induced (CD4i) epitopes that are essential for subsequent binding to chemokine receptor CCR5 or CXCR4. Due to their functional conservation, CD4i epitopes represent attractive viral targets for HIV-1 entry inhibition. The aim of the present study was to select peptide ligands for CD4i epitopes on native dualtropic (R5X4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…They enable studies without the need of using the native virus, which usually requires a higher safety level. Pseudotyping of retro-or lentiviral vectors is frequently used to study viral entry and to evaluate entry inhibitors (Siegert et al, 2005), or to harvest neutralizing antibodies at reduced safety levels (Schnierle et al, 1997;Seaman et al, 2010;Dervillez et al, 2010). It has been previously described that lentiviral vectors can be pseudotyped with CHIKV E1/E2 and transfer the CHIKV host range to these vectors (Salvador et al, 2009;Akahata et al, 2010;Kishishita et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They enable studies without the need of using the native virus, which usually requires a higher safety level. Pseudotyping of retro-or lentiviral vectors is frequently used to study viral entry and to evaluate entry inhibitors (Siegert et al, 2005), or to harvest neutralizing antibodies at reduced safety levels (Schnierle et al, 1997;Seaman et al, 2010;Dervillez et al, 2010). It has been previously described that lentiviral vectors can be pseudotyped with CHIKV E1/E2 and transfer the CHIKV host range to these vectors (Salvador et al, 2009;Akahata et al, 2010;Kishishita et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the N-terminal domain, especially from the CCR5 receptor, for gp120 binding led to the derivation of synthetic peptides inhibiting HIV entry in the micromolar range [74][75][76]. We could select an entry inhibitory peptide (XD3) with remarkable homology to the N-terminus of CCR5 and CXCR4 by phage display using CD4i epitopes on native dualtropic Env as target [77]. For CXCR4, which is less dependent on its N-terminus for HIV entry, we further designed a peptide comprising ECL1 to 3 linked to short spacers, which showed selective CXCR4 binding and entry inhibition in the low micromolar range [78].…”
Section: Hiv-1 Coreceptors Ccr5 and Cxcr4 And Inhibitors Of Coreceptomentioning
confidence: 99%
“…In a cellular HIV‐1 infection assay22 it was found that CX4‐M1 (IC 50 =9.93 μ M ), but not CX4‐M5 (IC 50 >50 μ M ), which presents only ECL2 of CXCR4, is able to interfere with the infection of cells with HIV‐1 with X4‐tropic HIV‐1 (HxBc2) (Table 1). This inhibitory effect was even slightly enhanced for the R183A and R188A variants of CX4‐M1 (CX4‐M6, IC 50 =5.14 μ M , and CX4‐M8, IC 50 =4.95 μ M ), which is in accordance with the ELISA binding data.…”
Section: Inhibition Of Infection Of Pm1 Cells With Pseudovirus Presenmentioning
confidence: 99%